Flows of newtonian and power-law fluids in symmetrically corrugated cappilary fissures and tubes - Walicka, Anna (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, an analytical method for deriving the relationships between the pressure drop and the volumetric flow rate in laminar flow regimes of Newtonian and power-law fluids through symmetrically corrugated capillary fissures and tubes is presented. This method, which is general with regard to fluid and capillary shape, can also be used as a foundation for different fluids, fissures and tubes. It can also be a good base for numerical integration when analytical expressions are hard to obtain due to mathematical complexities.
Keywords: power-law fluids; laminar flow; symmetrically corrugated capillaries; capillary fissures or tubes